2020
DOI: 10.1111/apt.15957
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of proton pump inhibitor therapy for eosinophilic oesophagitis in 630 patients: results from the EoE connect registry

Abstract: Background: Proton pump inhibitors (PPIs) are the most commonly used first-line therapy for patients with eosinophilic oesophagitis (EoE). However, many aspects related to PPIs in EoE are still unknown. Aims:To assess the effectiveness of PPI therapy for EoE in real-world practice. Methods:This cross-sectional study collected data on PPI efficacy from the multicentre EoE CONNECT database. Clinical remission was defined as a decrease of ≥50% in dysphagia symptom score; histological remission was defined as a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
88
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 46 publications
10
88
1
7
Order By: Relevance
“…A recent multicentre study by Laserna-Mendieta et al examined efficacy of PPI in maintaining clinico-histologic remission in patients with EoE and found that 30% of patients experience loss of response. While loss of response with PPI is not as high as that seen with topical steroids,33 this finding reiterates the need for continued assessment of clinical benefit, particularly for patients on maintenance therapy 34. Future studies might also examine how remission obtained on topical steroids versus dietary therapy impacts the chance of patients remaining on PPI therapy.According to consensus guidelines, patients with EoE who have responded to and are maintained on PPIs should undergo routine evaluation for sustained benefit, particularly given the risk of waning effect as is seen with other EoE therapies 33,35.…”
mentioning
confidence: 99%
“…A recent multicentre study by Laserna-Mendieta et al examined efficacy of PPI in maintaining clinico-histologic remission in patients with EoE and found that 30% of patients experience loss of response. While loss of response with PPI is not as high as that seen with topical steroids,33 this finding reiterates the need for continued assessment of clinical benefit, particularly for patients on maintenance therapy 34. Future studies might also examine how remission obtained on topical steroids versus dietary therapy impacts the chance of patients remaining on PPI therapy.According to consensus guidelines, patients with EoE who have responded to and are maintained on PPIs should undergo routine evaluation for sustained benefit, particularly given the risk of waning effect as is seen with other EoE therapies 33,35.…”
mentioning
confidence: 99%
“…To relieve concerns about the validity of our results, 1,2 DSS has been used in several studies, [3][4][5] including one carried out by Miehlke,6 because no validated instrument is available to assess symptoms in EoE patients in most European languages. DSS assesses frequency, intensity and duration of dysphagia; total scores range from 1 to 15.…”
Section: Editorsmentioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article. 2…”
Section: Ack N Owled G Em Entmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, we propose that the "real" effectiveness of PPI therapy in adult EoE patients should be regarded as limited unless proven otherwise by randomised placebo-controlled trials. Stephan Miehlke 1,2 Ulrike von Arnim 3 Stephen Attwood 4…”
mentioning
confidence: 99%